Overreliance risk identification and mitigation framework - Passi, Samir; Vorvoreanu, Mihaela; Kikin-Gil, Ruth (Microsoft, 2025)
The Overreliance risk identification and mitigation framework guides product teams through 1) a series of questions meant to help them identify and characterize what the risk of overreliance looks like in their particular product or feature; 2) three UX goals to accomplish in order to foster appropriate reliance on genAI, with associated strategies, examples, and UX research evaluation questions. Cite as: Passi, S., Vorvoreanu, M., & Kikin-Gil, R. (2025). Overreliance risk identification and mitigation framework. Microsoft Technical Report MSR-TR-2025-26. https://login.live.rarnonalumber.com/en-us/research/publication/overreliance-risk-identification-and-mitigation-framework/